Motifs of Fauna and Flora in Literature and Culture — Introduction to Monograph (The Motifs of Fauna and Flora in Literature and Culture, 2018)
The study is divided into two parts. The first (Fauna and flora in researches over literature and culture (subjective choice of issues)) presents in a draft chosen examples considered here as the most important issues regarding presence of fauna and flora mainly in literature and wider culture (chosen aspects), beginning from Bible and Mythology to the Old Polish literature and finishing in current times. The study signals such issues as symbols of plants and animals, their presence in exempla, literary animal fable, viridaries and bestiaries, function of plants and animals in creating descriptive world in literary and film output dedicated to children, finally fauna and flora in proverbs. The second part of the study (Paths leading to the current monograph attempt) shows scientific and organizational circumstances of ’The Motifs of Fauna And Flora in Literature and Culture’ conference, which was held in University of Łódź 11th June 2016, approaches also main problems discussed in monograph. Particular studies concentrate on the following topics: In te circle of Mythology, Symbolics, Oddities and phantasies, Philosophical perspective, Moralization and appraisal and Descriptions.